LANGUAGE STYLE IN MUFTI MENK KHUTBAH: BLESSING FROM THE OUTBREAK - Yasa Ayatina Ashidiq (LLDIKTI Wilayah X, 2023)
The society varies from a number of social backgrounds such as a various education, occupation, gender, religious belief etc. This variety became the core of language style. When choosing a style, the speaker can apply very formally or very informally, these choices are being governed by circumstance. Therefore, it needs to be studied in order to create the appropriate language style in speaking. Not only the research is expected to be useful for those who interested in the same field of language style research, but also it is expected for reader to know the type and the factors of language style to be used in real life conversation. This research used qualitative method which is suitable to language research. Then, this research used document analysis as a technique to collect the data and descriptive analysis as the technique of data analysis because it was appropriate for interpretating the data collected. Joos’ theory became the core to analyze the type of language style and its function. The research finding showed , there were 35 data of Mufi Menk utterances regarding the type of language style, there were divided into formal styles (11 data), frozen styles (12 data), consultative styles (5 data), and casual styles (7 data). For the function which influences Mufti Menk’s language choosing, there are two reasons: participant and topic. As the conclusion for this research, the researcher concludes that Mufti Menk used Formal style frequently in his speech in order to make the substance of the speech delivered.